The end of capitalism (as we knew it) : a feminist critique of political economy - Gibson-Graham, J. K. (University of Minnesota Press, 2006)
In the mid-1990s, at the height of discussion about the inevitability of capitalist globalization, J.K. Gibson-Graham presented a groundbreaking argument for envisioning alternative economies. This new edition includes an introduction in which the authors address critical responses to The End of Capitalism and outline the economic research and activism they have been engaged in since the book was first published.